Analyses of Tomato Fruit Brightness Mutants Uncover Both Cutin-Deficient and Cutin-Abundant Mutants and a New Hypomorphic Allele of GDSL Lipase. Issue 2 (19th December 2013) - Petit, Johann; Bres, Cécile; Just, Daniel; Garcia, Virginie; Mauxion, Jean-Philippe; Marion, Didier; Bakan, Bénédicte; Joubès, Jérôme; Domergue, Frédéric; Rothan, Christophe
Abstract : Opposite changes in the cutin polyester component in tomato fruit cuticle mutants lead to increased fruit glossiness . Abstract: The cuticle is a protective layer synthesized by epidermal cells of the plants and consisting of cutin covered and filled by waxes. In tomato ( Solanum lycopersicum ) fruit, the thick cuticle embedding epidermal cells has crucial roles in the control of pathogens, water loss, cracking, postharvest shelf-life, and brightness. To identify tomato mutants with modified cuticle composition and architecture and to further decipher the relationships between fruit brightness and cuticle in tomato, we screened an ethyl methanesulfonate mutant collection in the miniature tomato cultivar Micro-Tom for mutants with altered fruit brightness. Our screen resulted in the isolation of 16 glossy and 8 dull mutants displaying changes in the amount and/or composition of wax and cutin, cuticle thickness, and surface aspect of the fruit as characterized by optical and environmental scanning electron microscopy. The main conclusions on the relationships between fruit brightness and cuticle features were as follows: (1) screening for fruit brightness is an effective way to identify tomato cuticle mutants; (2) fruit brightness is independent from wax load variations; (3) glossy mutants show either reduced or increased cutin load; and (4) dull mutants display alterations in epidermal cell number and shape. Cuticle composition analyses further allowed the identification of groups of mutants displaying remarkable cuticle changes, such as mutants with increased dicarboxylic acids in cutin. Using genetic mapping of a strong cutin-deficient mutation, we discovered a novel hypomorphic allele of GDSL lipase carrying a splice junction mutation, thus highlighting the potential of tomato brightness mutants for advancing our understanding of cuticle formation in plants.